Hybrid treatment of black soldier fly larvae (Hermetia illucens) as a sustainable and efficient protein source in poultry diets. Issue 1 (May 2021) - Mohd Zuki, N. A.; Ibrahim, N. A.; Mat, K.; Rusli, N. D.; Harun, H. C.; Mahmud, M.; Samat, N.; Al-Amsyar, S. M.
Abstract: The purpose of this study was to investigate the potential of BSFL meal protein hydrolysate as a sustainable alternative source of protein in poultry diets. Protein hydrolysis of BSFL meal was carried out by using sodium chloride (NaCl), potassium chloride (KCl), and Thermostable Alkaline Protease enzyme (TAPzyme) under mild conditions: moderate temperature of 50 °C and pH 9. A total of 8 treatments: 10% NaCl (T1); 10% KCl (T2); 10% TAPzyme (T3); 20% TAPzyme (T4); 10% NaCl and 10% TAPzyme (T5); 10% NaCl and 20% TAPzyme (T6); 10% KCl and 10% TAPzyme (T7); and, 10% KCl and 20% TAPzyme (T8) were performed to determine protein hydrolysate concentration (μg/mL), and percentage of protein concentration decreased (%) at the end of this research. The hybrid treatment, i.e., Treatment 6 (10% NaCl and 20% TAPzyme), had the lowest protein concentration and highest protein concentration decreased at 280.782 µg/mL and 49.20%, respectively. This result shows that salt and protease's synergistic effect managed to hydrolysed BSFL protein into smaller peptides efficiently than salt and protease alone.